MHD natural convection in an enclosure from two semi-circular heaters on the bottom wall - Öztop, Hakan Fehmi; Rahman, M. M.; Ahsan, A.; Hasanuzzaman, M.; Saidur, R.; Al-Salem, Khaled; Rahim, N. A. (Pergamon-Elsevier Science Ltd, 2012)
A computational study of the thermal and dynamical behavior of fluid in an enclosure with two isothermal semi-circular heaters is presented. The top wall and the flat surfaces on bottom wall are adiabatic while the vertical walls are kept at lower temperature than the semi-circular heaters. The radius of curvature of the semi-circular surfaces is chosen as one tenth of the cavity wall length. The governing equations are solved by the Galerkin weighted residual finite element method. The effect of magnetic field on the flow is another important parameter in this study. Numerical simulations were performed for several values of Rayleigh number (10(3) <= Ra <= 10(6)), Hartmann number (0 <= Ha <= 50) and the distance between two semi-circular heaters (0.2 <= D <= 0.8). In all cases the Prandtl number is taken as 7. It is found that the distance between the semi-circular heaters is the most important parameter affecting the heat and fluid flow fields. In addition, Hartmann number was found to have an adverse affect on heat transfer. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Magnetohydrodynamics; Natural convection; Heat transfer; Semi-circular heater; Finite element method